2023
DOI: 10.1093/jscr/rjad093
|View full text |Cite|
|
Sign up to set email alerts
|

Acute pancreatitis after intragastric balloon insertion: case report

Abstract: The intragastric balloon (IGB) is a relatively recent non-surgical weight loss technique that is now widely used in the world to treat obesity. However, IGB causes a wide range of adverse effects that range from minor ones, such as nausea, stomach pain and gastroesophageal reflux, to serious ones, such as ulceration, perforation, intestinal blockage and compression of adjusting structures. A 22-year-old Saudi woman presented to the emergency department (ED) with a history of upper abdominal pain that started 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…While many of these cases were managed conservatively without the removal of the balloon, some of them required the removal of the balloon with or without other management strategies, along with standard inpatient management of acute pancreatitis. The prognosis has been generally excellent in all reported cases [9][10][11][12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…While many of these cases were managed conservatively without the removal of the balloon, some of them required the removal of the balloon with or without other management strategies, along with standard inpatient management of acute pancreatitis. The prognosis has been generally excellent in all reported cases [9][10][11][12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…The pooled AEs rate after Orbera from 68 studies showed that pain and nausea were frequent occurrences (33.7%), and early removal occurred in 7% of cases [22]. A concern that has been raised with fluidfilled balloons is their spontaneous hyperinflation and acute pancreatitis [23,24]. Albeit rare, early recognition and management are warranted.…”
Section: Orberamentioning
confidence: 99%